Sternal intraosseous schwannoma mimicking breast cancer metastasis - Igai, Hitoshi (BioMed Central, 2014)
The preoperative diagnosis of intraosseous schwannoma is challenging because of its rarity. We report a resected case of sternal intraosseous schwannnoma mimicking late recurrence of breast cancer. A 60-year-old Japanese woman with a history of breast cancer was diagnosed as having a sternal tumor by chest computed tomography (CT) demonstrating a round, well-defined, low-density nodule measuring 3.3 × 2.8 cm, which was located almost at the center of the sternum and associated with bone lysis and erosion. [(18) F]Fluorodeoxyglucose positron emission tomography (FDG-PET)/CT demonstrated FDG accumulation in the tumor, suggesting malignancy. Therefore, late isolated recurrence of breast cancer was suspected. Surgical resection was performed for both confirmation of the diagnosis and treatment. Pathological examination revealed that the tumor was composed predominantly of spindle-shaped cells arranged in a typical palisading pattern, being compatible with schwannoma. Although the periosteum was intact, the tumor was found to have destroyed the cortex of the sternum and proceeded forward to the bone marrow. Additionally, immunohistochemical staining revealed that the lesion was diffusely and strongly positive for S-100 protein. Thus metastasis from breast cancer was ruled out on the basis of the features revealed by microscopy.